2021
DOI: 10.3390/ijms22147715
|View full text |Cite
|
Sign up to set email alerts
|

Biodirected Synthesis of Silver Nanoparticles Using Aqueous Honey Solutions and Evaluation of Their Antifungal Activity against Pathogenic Candida Spp.

Abstract: Silver nanoparticles (AgNPs) were synthesized using aqueous honey solutions with a concentration of 2%, 10%, and 20%—AgNPs-H2, AgNPs-H10, and AgNPs-H20. The reaction was conducted at 35 °C and 70 °C. Additionally, nanoparticles obtained with the citrate method (AgNPs-C), while amphotericin B (AmB) and fluconazole were used as controls. The presence and physicochemical properties of AgNPs was affirmed by analyzing the sample with ultraviolet–visible (UV–Vis) and fluorescence spectroscopy, scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Nanoparticles (NPs) have been considered a useful way to enhance the hydrophilicity, antibacterial, and antifouling membrane properties [25][26][27]. AgNPs have been shown to be very active antibacterial agents [28] and antifungal agents [29][30][31] because of their high cytotoxic effect against a variety of microorganisms, especially in comparison with other metal nanoparticles [32] and antioxidants [33]. Recently, aqueous honey solutions with concentrations of 2%, 10%, and 20% were used to synthesize AgNPs to study their activity against fungi; the results show the activity of AgNPs against fungal is directly related to the concentration of honey utilized in their synthesis [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles (NPs) have been considered a useful way to enhance the hydrophilicity, antibacterial, and antifouling membrane properties [25][26][27]. AgNPs have been shown to be very active antibacterial agents [28] and antifungal agents [29][30][31] because of their high cytotoxic effect against a variety of microorganisms, especially in comparison with other metal nanoparticles [32] and antioxidants [33]. Recently, aqueous honey solutions with concentrations of 2%, 10%, and 20% were used to synthesize AgNPs to study their activity against fungi; the results show the activity of AgNPs against fungal is directly related to the concentration of honey utilized in their synthesis [31].…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs have been shown to be very active antibacterial agents [28] and antifungal agents [29][30][31] because of their high cytotoxic effect against a variety of microorganisms, especially in comparison with other metal nanoparticles [32] and antioxidants [33]. Recently, aqueous honey solutions with concentrations of 2%, 10%, and 20% were used to synthesize AgNPs to study their activity against fungi; the results show the activity of AgNPs against fungal is directly related to the concentration of honey utilized in their synthesis [31]. Ahsani and coworkers prepared modified PVDF and PVDF/Ag-SiO 2 membranes, where silica nanoparticles were used as a support for AgNPs to insure good separation and homogeneity of the nanocomposite [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effect of the honey dosage on the synthesis of NPs have also been performed. Czernel et al [ 53 ] demonstrated Ag-NPs synthesised using aqueous honey solutions at 2%, 10%, and 20% concentrations. The reaction was carried out at 35 °C and 70 °C.…”
Section: Application Of Honey-based Nanoparticles For Wound Dressingsmentioning
confidence: 99%
“…Because of their demonstrated capabilities as antibacterial, antiviral, and antifungal agents, AgNPs have been used in many biotechnology fields [ 40 , 41 ]. In addition, the concentration of honey employed in manufacturing AgNPs is directly correlated with the AgNPs’ antifungal action [ 42 ]. Silver nitrate is reduced by the use of honey and also acts as a stabilizing mediator for AgNPs created as part of an environmentally friendly process for fabricating silver nanoparticles (AgNPs) at low temperatures [ 43 ].…”
Section: Introductionmentioning
confidence: 99%